O canto educativo das sereias: formação e pluralidade de perspectivas - Ourique, Maiane Liana Hatschbach (2007)
This work argues the relation unit-plurality from the formative proposal of the education. The education preserves - when aiming at an individual former of the world a vigorous relation with the transcendental thinking. So that, the school, place for excellence of the cultural formation (Bildung), is lost in the diagnosis of crisis of its function. Considering the new contours of the reason, acquired with the linguistic turn, this research is guided for the following question: it is possible still to keep the speech of the formation (Bildung) in the context of plurality of the perspective contemporaries who pass by the education? In the attempt to reintegrate the dimensions practical-moral and aesthetic-expressive with the reason, Habermas waves with the concept of a reason incorporated in communicative act. At the same time where he doesn t deny the conquests and the modern normative content, he delineates a situated reason, where the unit is the perspective of approach and not a condition given beforehand. With the pragmatic of the language, the pedagogical ends to link with the form to comprehend the knowledge and the subject in the education. The Habermas idea - of that it has a unit in the plurality - allows to understand the own project of the Bildung as plural. Thus, the totalitarian universality of the Bildung is retired to understand it as thought exercise. Therefore, this research concluded that it s not necessary to abandon the proposal of the Bildung to understand the different perspectives contemporaries who cross the education. These perspectives, sheltered in the different narratives of the quotidian, contribute in the understanding of the world, binding the circumscribed elements in the formative process